The Implementation of Sequential Picture Media with Chain Story Technique to Improve Speaking Skills in Grade IV of SDN 5 Palangka - Itasni, Karmi; Diplan, Diplan; Shukuri, Hakan; Enjeli, Enjeli; Pribadi, Fachriza Adji (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2025)
This study aims to determine the description of the process of implementing serial picture media with a chain story technique so that it can improve the speaking skills of class IV students of SDN 5 Palangka and to determine the improvement of students' speaking skills through the application of serial picture media with a chain story technique in class IV students of SDN 5 Palangka. This study was conducted using classroom action research carried out at SDN 5 Palangka. The subjects of this study were class IV students of SDN 5 Palangka in the 2024/2025 Academic Year. The data collection technique used was Observation and Test Data analysis using classical value percentage calculations with a success indicator of 70% for student learning outcomes. The results of the study, namely the results of the initial speaking skills test, the average value was 63.42 with the criteria of being less achieved and classical completeness of 36.84%, this criterion is included in the very poor category, in cycle I the test results with classical values ​​became 63.15% and an average score of 70.15. In cycle II, there was an increase in learning outcomes, namely an increase to 89,48% with an average of 81,47, namely 16 people were in the completed category and 3 students were in the incomplete category. The implementation of learning activities by applying a series of picture media with a chain story technique in each teacher activity and student activity was also carried out well. The results of student activities in cycle I were 2.43 with a sufficient category, in cycle II there was an increase to 3.06 with a good category. The results of teacher activities in cycle I were 2.61 with a sufficient category then in cycle II there was an increase to 3.18 and a good category. This shows that teachers can manage learning by applying a series of picture media with a chain story technique well.